2020
DOI: 10.1186/s13014-020-01564-w
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic body radiation therapy in the treatment of ovarian cancer

Abstract: Background This study evaluates the outcomes and toxicity of stereotactic body radiation therapy (SBRT) in ovarian cancer. Methods This retrospective analysis considered all patients treated with SBRT from 2009 to 2018 with a primary ovarian tumor. Follow-up included PET-CT and CT scans at 2–3 month intervals. Statistical analysis primarily consisted of univariate analysis, Cox proportional hazards analysis, and the Kaplan-Meier method. Results The study included 35 patients with 98 treatments for lymph node… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…In 2020, Kowalchuk et al published a retrospective analysis of 35 ovarian cancer patients with 98 treated lesions to review the toxicity and outcomes of stereotactic radiotherapy in ovarian cancer. They drew similar conclusions to previous studies, that stereotactic radiotherapy was safe with only one toxicity greater than grade 2 (grade 5 late bowel toxicity with gastrointestinal bleeding) and also effective, with 2-year local control rates of 80% 35…”
Section: Radiotherapy In Relapse: Stereotactic Radiotherapysupporting
confidence: 79%
See 1 more Smart Citation
“…In 2020, Kowalchuk et al published a retrospective analysis of 35 ovarian cancer patients with 98 treated lesions to review the toxicity and outcomes of stereotactic radiotherapy in ovarian cancer. They drew similar conclusions to previous studies, that stereotactic radiotherapy was safe with only one toxicity greater than grade 2 (grade 5 late bowel toxicity with gastrointestinal bleeding) and also effective, with 2-year local control rates of 80% 35…”
Section: Radiotherapy In Relapse: Stereotactic Radiotherapysupporting
confidence: 79%
“…They drew similar conclusions to previous studies, that stereotactic radiotherapy was safe with only one toxicity greater than grade 2 (grade 5 late bowel toxicity with gastrointestinal bleeding) and also effective, with 2-year local control rates of 80%. 35 The excellent rates of local control with stereotactic radiotherapy in oligometastatic gynecological malignancy is promising for the future; however, significant rates of disease progression outside of the radiation field still exist (79-100% of failures). For this reason, careful consideration and patient selection is required to decide whether to treat nodal recurrences with highly focal stereotactic radiotherapy or a more extensive involved field radiation which runs the risk of greater toxicity.…”
Section: Radiotherapy In Relapse: Stereotactic Radiotherapymentioning
confidence: 99%
“…34 Another retrospective study including 35 patients with oligometastatic ovarian cancer treated with SBRT yielded a 2-year lesional control of 80%, with a higher dose (BED >35 Gy) associated with improved control. 35 A retrospective study including 20 patients (10 ovarian and 10 uterine) with a single metastatic site treated with SBRT revealed that patients with smaller tumors (<50 mL) had improved local control (5-year local control <50 mL 100% vs >50 mL 65%; p<0.02). 36 In a prospective phase II trial evaluating the efficacy of SBRT in 49 patients with metastatic gynecologic tumors, there was a 96% response rate in the treated lesions with a median PFS of 7.8 months and overall survival of 20.2 months.…”
Section: Sbrt In Gynecologic Oligometastasesmentioning
confidence: 99%
“…In one study reporting 82 patients diagnosed with ovarian cancer with 156 metastatic lesions treated with SBRT, control of the treated lesions at 2 years was found to be 68% and the median systemic treatment-free interval after SBRT was 7.4 months 34. Another retrospective study including 35 patients with oligometastatic ovarian cancer treated with SBRT yielded a 2-year lesional control of 80%, with a higher dose (BED >35 Gy) associated with improved control 35. A retrospective study including 20 patients (10 ovarian and 10 uterine) with a single metastatic site treated with SBRT revealed that patients with smaller tumors (<50 mL) had improved local control (5-year local control <50 mL 100% vs >50 mL 65%; p<0.02) 36…”
Section: Sbrt In Gynecologic Oligometastasesmentioning
confidence: 99%
“…The effectiveness of SBRT on LC is clearly associated with a doseresponse correlation; higher biologically equivalent dose (BED) leads to better tumor control (71,72). For lymph node metastases, 5year LC rates of uterine, cervical, and ovarian cancer range from 70 to 97%, and favorable disease-free survival and overall survival are reported in retrospective series (64,68,70,(72)(73)(74)(75)(76)(77). Lymph node metastases of gynecologic malignancies are often located in the pelvis or abdomen, where conventional SBRT using CBCT image guidance yields relatively poor soft tissue contrast.…”
Section: Omrgrt In the Management Of Oligometastatic Lymph Node Metastases From Gynecologic Malignanciesmentioning
confidence: 99%